Modification of the B meson mass in a magnetic field from QCD sum rules - Machado, C. S. [UNESP]; Matheus, R. D. [UNESP]; Finazzo, S. I. [UNESP]; Noronha, J. [UNESP] (American Physical Society (APS), 2014)
In this paper, we extend the well-known QCD sum rules used in the calculation of the mass of heavy mesons to estimate the modification of the charged B-meson mass, mB, in the presence of an external Abelian magnetic field, eB. Two simplifying limits were considered: the weak field limit, in which the external field satisfies eBm2 (with m being any of the masses involved); and the strong field limit, in which the field strength is small in comparison to the bottom quark mass (or the B-meson mass) squared, but it is large compared to the mass of the light quarks, i.e., mu,d2eBmb,B2. We found that mB decreases with the magnetic field in both of these limits. © 2014 American Physical Society.